A Thermochemical Parameters and Theoretical Study of the Chlorinated Compounds of Thiophene - Ibrahim A. M. Saraireh; Mohammednoor Altarawneh; Jibril Alhawarin; Mansour H. Almatarneh (Heteroatom Chemistry)
This contribution sets out to compute thermochemical and geometrical parameters of the complete series of chlorinated isomers of thiophene based on the accurate chemistry model of CBS-QB3. Herein, we compute standard entropies, standard enthalpies of formation, standard Gibbs free energies of formation, and heat capacities. Our calculated enthalpy values agree with available limited experimental values. The DFT-based reactivity descriptors were used to elucidate the site selectivity for the chlorination sequence of thiophene. The relative preference for chlorination was found to be in accord with the thermodynamic stability trends inferred based on the H scale. Calculated Fukui indices predict a chlorination sequence to ensue as follows: 2-chloro → 2,5-dichloro → 2,3,5-trichloro → 2,3,4,5-tetrachlorothiophene.